2010
DOI: 10.1093/hmg/ddp585
|View full text |Cite
|
Sign up to set email alerts
|

The snoRNA MBII-52 (SNORD 115) is processed into smaller RNAs and regulates alternative splicing

Abstract: The loss of HBII-52 and related C/D box small nucleolar RNA (snoRNA) expression units have been implicated as a cause for the Prader-Willi syndrome (PWS). We recently found that the C/D box snoRNA HBII-52 changes the alternative splicing of the serotonin receptor 2C pre-mRNA, which is different from the traditional C/D box snoRNA function in non-mRNA methylation. Using bioinformatic predictions and experimental verification, we identified five pre-mRNAs (DPM2, TAF1, RALGPS1, PBRM1 and CRHR1) containing alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
281
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 260 publications
(293 citation statements)
references
References 34 publications
5
281
0
5
Order By: Relevance
“…The presence of SNORD27 in nuclear fractions devoid of fibrillarin suggests that it has a function apart from rRNA 2′-O-methylation. We previously found that the orphan SNORD115 changes alternative splicing of the serotonin receptor 2C and several other premRNAs, possibly through base pairing of SNORD115 to a splicing regulatory region (31,51). We, therefore, looked for complementarities between SNORD27 and pre-mRNAs across the genome.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of SNORD27 in nuclear fractions devoid of fibrillarin suggests that it has a function apart from rRNA 2′-O-methylation. We previously found that the orphan SNORD115 changes alternative splicing of the serotonin receptor 2C and several other premRNAs, possibly through base pairing of SNORD115 to a splicing regulatory region (31,51). We, therefore, looked for complementarities between SNORD27 and pre-mRNAs across the genome.…”
Section: Resultsmentioning
confidence: 99%
“…3 Recent new cellular functions have led us to hypothesize that snoRNA accumulation patterns could be modulated in cancer. [10][11][12]14,[30][31][32][33][34][35] Acute leukemia is a good model to try to answer this question as it is characterized by restrictive oncogenic events leading to a blockade in differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the main function of snoRNA is to guide chemical modifications of other RNAs, some of them or their fragments can regulate splicing or translation (Kishore et al 2010;Scott et al 2012;Stepanov et al 2012). While some (in particular, H/ACA box) snoRNAs interact with their rRNA targets by small bipartite recognition sites, the known cases of splicing regulation contain long, uninterrupted helices.…”
Section: Snorna Targetsmentioning
confidence: 99%